P612 Lack of seroconversion following COVID-19 vaccination, but not treatment, is an independent risk factor for breakthrough SARS-CoV-2 infection in patients with inflammatory bowel disease: data from ESCAPE - an IG-IBD Study. (30th January 2023) - Macaluso, F S; Principi, M; Facciotti, F; Contaldo, A; Todeschini, A; Bezzio, C; Saibeni, S; Castiglione, F; Nardone, O M; Spagnuolo, R; Fantini, M C; Riguccio, G; et al.
Abstract: Background: As patients with immune conditions were excluded from COVID-19 vaccine clinical trials, it is important to accumulate real-world data in this setting, particularly to identify those who would benefit from repeated doses. Methods: E ffectiveness and S afety of C OVID-19 Va ccine in P atie nts with Inflammatory Bowel Disease (IBD) Treated with Immunomodulatory or Biological Drugs (ESCAPE) is a prospective, multicentre, observational study assessing effectiveness and safety of COVID-19 vaccines in patients with IBD (ClinicalTrials.gov ID: NCT04769258). Here we present data on the rate of breakthrough SARS-CoV-2 infections in the timeframe between 14 days after the second dose and the third dose of COVID-19 vaccine (or a maximum of 9 months from the second dose). The risk factors for SARS-CoV-2 infection, including lack of seroconversion (cut-off for IgG anti-SARS-CoV-2: OD 0.28) and IgG anti-SARS-CoV-2 levels after 8 weeks from the second dose, and treatment for IBD, were assessed. Results: Out of the 1076 patients with IBD enrolled in the ESCAPE study, data on breakthrough SARS-CoV-2 infection were available in 953 cases. Most of the patients received homologous, double-dose mRNA-based vaccines (BNT162b2 or mRNA-1273: 99.2%). Seroconversion was reported in 92.7% of cases (median OD 1.60 [IQR 0.8-3.6]), while SARS-CoV-2 infection was documented in 95 patients (10.0%), of whom 9 died. At multivariable regression analyses, age (OR 0.97, 95% CI 0.96-0.99; p<0.001) being former smoker (OR 2.23, 95% CI 1.26-3.88; p=0.005), and lack of seroconversion (OR 0.42, 95% CI 0.20-0.99; p=0.034) were independent predictors of SARS-CoV-2 infection. Conversely, none of the treatments for IBD was associated with breakthrough SARS-CoV-2 infection. Notably, all 9 patients who died had reported seroconversion after the second dose. Conclusion: IBD patients without seroconversion after COVID-19 vaccines are at increased risk for SARS-CoV-2 infection, while medications for IBD had no impac